Influence of LEED branding on building occupants' pro-environmental behavior. (December 2015) - Khashe, Saba; Heydarian, Arsalan; Gerber, David; Becerik-Gerber, Burcin; Hayes, Timothy; Wood, Wendy
Abstract: In this paper, we examine the influence of branding a building as LEED certified on occupants' pro-environmental behavior (individual participation in an activity that promotes sustainable (green) practices by reducing or eliminating negative environmental impacts). Branding is defined as identifying a building as LEED certified and emphasizing the aspects of the building's green features to its users. One hundred participants were randomly assigned to one of the two experimental groups: (1) the branding group, in which the building was branded as being LEED certified, and (2) the control group, in which no information was provided about the building being LEED certified. Through the use of an immersive virtual environment, two examples of pro-environmental behaviors were examined between the two groups: participants' choices in using natural light vs. artificial light for increasing the lighting levels in the room, as well as their choices of recycling bin vs. regular trashcan for placing scrap paper. The results show that the participants in the branding group chose natural light and recycling bin significantly more than the participants in the control group, suggesting that LEED branding motivates occupants' pro-environmental behaviors. The results also show that participants' environmental values and views had significant effects on the influence of LEED branding. The results also suggest that increasing building occupants' knowledge about environmental issues might improve their pro-environmental behaviors. Highlights: We examined the influence of LEED branding on building occupants' behaviors. LEED branding positively affects occupants' energy consumption behaviors. LEED branding positively affects occupants' environmental behaviors. LEED branding is more effective on environmentally conscious occupants.